Dominant negative inhibition by fragments of a monomeric enzyme - Michaels, John-Edward A. (The National Academy of Sciences of the USA, 1996)
Dominant negative inhibition is most commonly seen when a mutant subunit of a multisubunit protein is coexpressed with the wild-type protein so that assembly of a functional oligomer is impaired. By analogy, it should be possible to interfere with the functional assembly of a monomeric enzyme by interfering with the folding pathway. Experiments in vitro by others suggested that fragments of a monomeric enzyme might be exploited for this purpose. We report here dominant negative inhibition of bacterial cell growth by expression of fragments of a tRNA synthetase. Inhibition is fragment-specific, as not all fragments cause inhibition. An inhibitory fragment characterized in more detail forms a specific complex with the intact enzyme in vivo, leading to enzyme inactivation. This fragment also associated stoichiometrically with the full-length enzyme in vitro after denaturation and refolding, and the resulting complex was catalytically inactive. Inhibition therefore appears to arise from an interruption in the folding pathway of the wild-type enzyme, thus suggesting a new strategy to design dominant negative inhibitors of monomeric enzymes.